2019
DOI: 10.1002/psp4.12446
|View full text |Cite
|
Sign up to set email alerts
|

Application of Physiologically‐Based and Population Pharmacokinetic Modeling for Dose Finding and Confirmation During the Pediatric Development of Moxifloxacin

Abstract: Moxifloxacin is a widely used fluoroquinolone for the treatment of complicated intra‐abdominal infections. We applied physiologically‐based pharmacokinetic (PBPK) and population pharmacokinetic (popPK) modeling to support dose selection in pediatric patients. We scaled an existing adult PBPK model to children based on prior physiological knowledge. The resulting model proposed an age‐dependent dosing regimen that was tested in a phase I study. Refined doses were then tested in a phase III study. A popPK analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Figure shows the single‐dose exposure (expressed as area under the concentration‐time curve [AUC]) predicted for children with a PBPK model in comparison to the data observed in the first clinical trial with rivaroxaban in children . Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials . In both case examples, PBPK modeling in children using previous ontogeny information has been proven to be very helpful to guide the development of suitable dosing regimens in pediatric development programs.…”
Section: Application Of Pbpk In Pediatric Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the single‐dose exposure (expressed as area under the concentration‐time curve [AUC]) predicted for children with a PBPK model in comparison to the data observed in the first clinical trial with rivaroxaban in children . Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials . In both case examples, PBPK modeling in children using previous ontogeny information has been proven to be very helpful to guide the development of suitable dosing regimens in pediatric development programs.…”
Section: Application Of Pbpk In Pediatric Researchmentioning
confidence: 99%
“…25 Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials. [26][27][28] In both case examples, PBPK modeling in children using previous ontogeny information has been proven to be very helpful to guide the development of suitable dosing regimens in pediatric development programs.…”
Section: Established Ontogeny Functionsmentioning
confidence: 99%
“…Additional maturational processes, particularly phase I and phase II enzyme ontogeny, may have to be considered in children younger than two years of age for small molecule drugs. This has given rise to more complex approaches, including physiologically based pharmacokinetic (PBPK) models for which there is meanwhile considerable experience with scaling PBPK models to pediatric populations for small molecule drugs (Leong et al, 2012;Templeton et al, 2018;Heimbach et al, 2019;Willmann et al, 2019). For therapeutic proteins like antibodies, however, there is currently only very limited experience with scaling PBPK models to children (Hardiansyah and Ng, 2018;Hanke et al, 2019;Malik and Edginton, 2019;Malik and Edginton, 2020), and there is currently only limited quantitative information regarding the maturation of the processes relevant for antibody PK (Shi and Derendorf, 2010;Xu et al, 2013;Edlund et al, 2015;Zhang et al, 2015;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The PBPK models for amikacin, gadovist, and magnevist were updated to PK‐Sim version 9, 20,21 as additional simulations needed to be performed for this analysis, which is described in more detail below. As the developed PBPK models that were applied for clinical decision making have been filed for regulatory request, most of these models are also already published, whereas some of them are still part of the ongoing drug development program 3,12–17 …”
Section: Methodsmentioning
confidence: 99%
“…Both intravenous and orally administered ciprofloxacin PK data were available for analysis. To reflect the known elimination pathways of ciprofloxacin, 17 the PBPK model included renal clearance and hepatic clearance. The renal clearance processes were glomerular filtration and an unspecific tubular secretion (TS) accounting for the exceeding renal clearance 29,30 .…”
Section: Methodsmentioning
confidence: 99%